2021
DOI: 10.3389/fnagi.2021.692911
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Diabetic Retinopathy and Cognitive Impairment: A Systematic Review and Meta-Analysis

Abstract: Diabetic retinopathy (DR) is one of the most common microvascular complications associated with diabetes mellitus. However, its correlation with another diabetes-related disorder, cognitive impairment, has not been well studied. This systematic review and meta-analysis aimed to explore the association between DR and cognitive impairment. MEDLINE (PubMed), the Cochrane Library, and EMBASE databases were searched for observational studies that reported an association between DR and cognitive impairment. Data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
8
0
5
Order By: Relevance
“…To this end, they found that patients with DR had increased prevalence (Ong et al, 2012 ; Liao et al, 2017 ) and incidence (Gupta et al, 2019 ) of CIND, as well as increased incidence of AD (Chen et al, 2016 ; Lee et al, 2019 ; Pedersen et al, 2022 ). A recent systematic review and meta-analysis support these results by concluding that having moderate DR or worse was strongly associated with cognitive impairment (Cheng et al, 2021 ). Considered in tandem with the findings of our study, this suggests that the association between DR and cognitive impairment may be bidirectional.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…To this end, they found that patients with DR had increased prevalence (Ong et al, 2012 ; Liao et al, 2017 ) and incidence (Gupta et al, 2019 ) of CIND, as well as increased incidence of AD (Chen et al, 2016 ; Lee et al, 2019 ; Pedersen et al, 2022 ). A recent systematic review and meta-analysis support these results by concluding that having moderate DR or worse was strongly associated with cognitive impairment (Cheng et al, 2021 ). Considered in tandem with the findings of our study, this suggests that the association between DR and cognitive impairment may be bidirectional.…”
Section: Discussionmentioning
confidence: 87%
“…Overall, past studies focused overwhelmingly on western populations, reflecting a paucity of data on other races/ethnicities. While several studies have examined the impact of having DR on cognitive impairment (Cheng et al, 2021 ), no studies have examined the impact of having cognitive impairment on DR. Finally, very limited data are available on the impact of CIND on eye diseases, a condition with established risk of progression to AD and other forms of dementia (Petersen, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Изучение взаимосвязей между выраженностью иммунологических изменений и когнитивными нарушениями у пациентов с диабетической ретинопатией представляет одну из актуальных проблем современной иммунологии [5,6]. Несколько исследований анализировали связь диабетической ретинопатии с когнитивными нарушениями, показав противоречивые результаты [3]. Так, в недавнем метаанализе [3], включившим в себя 15 исследований из базы данных MEDLINE, отношение шансов ассоциации диабетической ретинопатии с когнитивными нарушениями составило 2,24 при 95% доверительном интервале 1,89-2,66.…”
Section: Discussionunclassified
“…Несколько исследований анализировали связь диабетической ретинопатии с когнитивными нарушениями, показав противоречивые результаты [3]. Так, в недавнем метаанализе [3], включившим в себя 15 исследований из базы данных MEDLINE, отношение шансов ассоциации диабетической ретинопатии с когнитивными нарушениями составило 2,24 при 95% доверительном интервале 1,89-2,66. Однако в исследовании [9], выполненном на большой группе пациентов с диабетической ретинопатией, не обнаружено связи между диабетической ретинопатией и ухудшением когнитивных функций.…”
Section: Discussionunclassified
“…Неоспоримо ведущая роль диабетической ретинопатии (ДР) как причина слепоты у лиц трудоспособного и пожилого возраста наблюдается в настоящее время во многих развитых странах [2,5,7]. ДР -это наиболее распространенное микрососудистое осложнение сахарного диабета, встречающееся приблизительно у 29% взрослых с диабетом 2-го типа и 95% людей с диабетом 1-го типа [6].…”
Section: Introductionunclassified